2022
DOI: 10.3390/su14159119
|View full text |Cite
|
Sign up to set email alerts
|

Loss Aversion Order Strategy in Emergency Procurement during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has had a serious impact on firms’ sourcing strategies. Since COVID-19 disrupted the supply chain, firms have had to make emergency purchases from other suppliers. In addition, emergency ordering is one of the most effective strategies to achieve sustainable operations because such a strategy can save inventory costs. We aim to address a retailer’s emergency procurement strategies during the COVID-19 pandemic. We use prospect theory and the newsvendor model to uncover the retailer’s inven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Research has also shown that past buying experience (PBE) can influence PB behaviour. Zhang et al (2022) found that individuals who had prior experience with PB were more likely to engage in PB during the pandemic. Similarly, in a study on PB behaviour during the H1N1 pandemic, Lau et al (2010) found that individuals who had previous experience with PB were more likely to engage in PB behaviour.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 92%
See 1 more Smart Citation
“…Research has also shown that past buying experience (PBE) can influence PB behaviour. Zhang et al (2022) found that individuals who had prior experience with PB were more likely to engage in PB during the pandemic. Similarly, in a study on PB behaviour during the H1N1 pandemic, Lau et al (2010) found that individuals who had previous experience with PB were more likely to engage in PB behaviour.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 92%
“…In the case of PB, the PS and PR act as external stimuli that create an internal state of heightened arousal among individuals, leading to the behavioural response of PB (Zhang et al , 2022). The COVID-19 pandemic has led to numerous stress-related disorders like stress and anxiety (Qiu et al , 2020; Wang et al , 2020a; Xiang et al , 2020), and among these, PR is found to have a significant relationship with people’s behaviour during the pandemic, particularly the PB behaviour of customers (Taghrir et al , 2020).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…For example, one impact of the pandemic was supply chain shortages. Huang, Li, and Liu studied the emergency procurement strategies of companies under the impact of COVID-19 [14]. The newsvendor model plays an important role in operations management.…”
Section: Loss Aversion In the Emergency Procurementmentioning
confidence: 99%
“…p denotes the selling price. According to their proof, when λ = 1 as well as e = p, the classical newsvendor model becomes a model with emergency procurements and loss aversion [14].…”
Section: Loss Aversion In the Emergency Procurementmentioning
confidence: 99%
See 1 more Smart Citation